Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The impact of using mobile learning on academic achievement and the development of expressive reading skills in the English language course for secondary school students in the city of JeddahMr. Abdullah Yahya Albaeth2. The classroom management issues faced by early childhood teachersMs. Sharefah Saad Algamdi3. The reality of using virtual laboratory in Madrasati platform for Chemistry subject teachers in secondary schools in RiyadhMr. Abdallah Saltan Al-Baqami, Dr. Turki Saad Al-Zahrani4. The role of Employing e-learning in integrating students with learning difficulties with ordinary students from the point of view of basic stage teachers in South Hebron DirectorateDr. Feryal Abdulaziz Amro, Mrs. Maryam Rafieq Al-Hamouri5. Psychometric Characteristics of Sustainable Behaviour Metric for Middle School StudentsMs. Fatima Abdullah Al-Shahrani, Co-Prof. Nawal Gram Allah Al-Ghamdi6. Psychological Stress among Mothers of Autistic Children in light of Counseling Services provided to them in Al-MadinahMs. Waad Abdul-Karim Al-Mutairi7. Job compatibility among kindergarten principals in the State of Kuwait  from the teachers' point of viewDr. Amna Haidar Al-Hearz
Keywords: Journal of Educational and Psychological Sciences